2023
DOI: 10.1038/s41598-023-28163-5
|View full text |Cite
|
Sign up to set email alerts
|

Detecting type 2 diabetes mellitus cognitive impairment using whole-brain functional connectivity

Abstract: Type 2 diabetes mellitus (T2DM) is closely linked to cognitive decline and alterations in brain structure and function. Resting-state functional magnetic resonance imaging (rs-fMRI) is used to diagnose neurodegenerative diseases, such as cognitive impairment (CI), Alzheimer’s disease (AD), and vascular dementia (VaD). However, whether the functional connectivity (FC) of patients with T2DM and mild cognitive impairment (T2DM-MCI) is conducive to early diagnosis remains unclear. To answer this question, we analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 68 publications
0
0
0
Order By: Relevance
“…The results showed that the nomogram achieved high accuracy in predicting T2DM risk and could be clinically applicable for the early detection and prevention of T2DM. Another study by Wu et al ( 2023) [32] proposed a novel machine learning algorithm that combines deep neural networks (DNNs) and attention mechanisms to predict T2DM. The authors used electronic health record data from a large hospital in China and compared their model's performance to other widely used models.…”
Section: Khallel Et Al (2021)mentioning
confidence: 99%
“…The results showed that the nomogram achieved high accuracy in predicting T2DM risk and could be clinically applicable for the early detection and prevention of T2DM. Another study by Wu et al ( 2023) [32] proposed a novel machine learning algorithm that combines deep neural networks (DNNs) and attention mechanisms to predict T2DM. The authors used electronic health record data from a large hospital in China and compared their model's performance to other widely used models.…”
Section: Khallel Et Al (2021)mentioning
confidence: 99%